Methodological procedure for the determination of the motor skill invariants of the long jump in sport initiation/Procedimiento metodológico para la determinación de las invariantes de habilidades motrices del salto de longitud en la iniciación deportiva - Hiramnia Mabel Sánchez Acosta; Agnie Sánchez Acosta; Alberto Bautista Sánchez Oms (Podium, 2021)
Studies carried out in different countries show that internal-biological and external-social characteristics determine the pace of learner development. However, after an evaluation of the Athletics Education Program, it was found that the selection of tasks, the growth and development of the athlete, his/her participation in social life as a citizen and the changes in knowledge, skills, feelings and convictions have not been taken into account. That is why the present study was developed, with a view to determine the invariants of motor skills in correspondence with the development of the external and internal characteristics of long jumpers in sports initiation. For this study, methods such as documentary review, interview, survey and the criteria of specialists and users, as well as interactive techniques were used, which made possible to conform the methodological procedure, which gives a different vision to the way in which the abilities are selected for the teaching-learning process of the Long Jump at present.